Adversities of development : a case study of involuntary resettlement - Rahman, Khondker Neaz. (Dhaka : Academic Press and Publishers, 2004)
With reference to Bangladesh; includes articles on applicability of relevant laws.
Includes bibliographical references (p. [48]-50).
Appendices in English and Bengali.
Keywords: Forced migration -- Bangladesh -- Sirājganj District; Forced migration -- Bangladesh -- Bogra District; City planning and redevelopment law -- Bangladesh